PENERAPAN HOME VISIT UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SDN 037 TARAKAN - Nur Qayyumi Yuniaty; Suriata Suriata; Nisa Ariantini (Jurnal Bimbingan dan Konseling Borneo, 2023)
AbstractThis study aims to examine "Implementation of Home Visits to Increase Student Interest in Learning". This type of research is qualitative with a case study approach. In this study, data sources consist of primary data and secondary data. Primary data sources were 2 students participating in home visit services and class VI-A teachers. Secondary data sources are parents, school principals, and supporting documents for this study. Interviews, observations, and documentation were used as data collection techniques. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that the home visit service carried out by class VI-A teachers at SD Negeri 037 Tarakan was effective in increasing students' interest in learning. Class VI-A teachers conduct home visit services according to the Operational Guidance and Counseling Guidelines for Elementary Schools (POP BK SD) with several stages consisting of the preparation stage, the implementation stage, the final stage of the home visit, and the reporting stage of the home visit. In the preparation stage, the class teacher analyzes and focuses on the problems experienced by students. Then, the class teacher communicates with the student's parents regarding the plan to carry out the home visit. The class teacher must get an assignment letter from the school principal. At the implementation stage, class teachers meet with parents to discuss problems experienced by students. At the end of the home visit, the class teacher and parents held a discussion regarding the student's learning interest issues that had to be resolved during the home visit. At the home visit reporting stage, the class teacher reports the results of the home visit to the school principal.Keywords : Home visit, learning interestAbstractPenelitian ini bertujuan untuk mengkaji “Pelaksanaan Home Visit untuk Meningkatkan Minat Belajar Siswa”. Jenis penelitian ini adalah kualitatif dengan pendekatan study kasus. Dalam penelitian ini, sumber data terdiri dari data primer dan data sekunder. Sumber data primer adalah 2 siswa peserta layanan kunjungan rumah dan guru kelas VI-A. Sumber data sekunder adalah orang tua, kepala sekolah, dan dokumen pendukung penelitian ini. Wawancara, observasi, dan dokumentasi digunakan sebagai teknik pengumpulan data. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa layanan kunjungan rumah yang dilaksanakan oleh guru kelas VI-A SD Negeri 037 Tarakan efektif untuk meningkatkan minat belajar siswa. Guru kelas VI-A melakukan pelayanan kunjungan rumah sesuai Pedoman Operasional Bimbingan dan Konseling Sekolah Dasar (POP BK SD) dengan beberapa tahapan yang terdiri dari tahap persiapan, tahappelaksanaan, tahap akhir kunjungan rumah, dan pelaporan tahap kunjungan rumah. Pada tahap persiapan, guru kelas menganalisis dan memfokuskan pada permasalahan yang dialami siswa. Kemudian, guru kelas berkomunikasi dengan orang tua siswa terkait rencana pelaksanaan kunjungan rumah. Guru kelas harus mendapatkan surat tugas dari kepala sekolah. Pada tahap implementasi, guru kelas bertemu dengan orang tua untuk membahas permasalahan yang dialami siswa. Pada akhir kunjungan rumah, guru kelas dan orang tua mengadakan diskusi mengenai masalah minat belajar siswa yang harus diselesaikan selama kunjungan rumah. Pada tahap pelaporan kunjungan rumah, guru kelas melaporkan hasil pelaksanaan kunjungan rumah kepada kepala sekolah.Kata Kunci : Home visit, minat belajar